Decreasing resilience of China's coupled nitrogen-phosphorus cycling network requires urgent action - Luo, Zimeng; Yu, Yadong; Kharrazi, Ali; Fath, Brian D; Matsubae, Kazuyo; Liang, Sai; Chen, Dingjiang; Zhu, Bing; Ma, Tieju; Hu, Shanying (Nature food, 2024)
The coupled nature of the nitrogen (N) and phosphorus (P) cycling networks is of critical importance for sustainable food systems. Here we use material flow and ecological network analysis methods to map the N-P-coupled cycling network in China and evaluate its resilience. Results show a drop in resilience between 1980 and 2020, with further decreases expected by 2060 across different socio-economic pathways. Under a clean energy scenario with additional N and P demand, the resilience of the N-P-coupled cycling network would suffer considerably, especially in the N layer. China's socio-economic system may also see greater N emissions to the environment, thus disturbing the N cycle and amplifying the conflict between energy and food systems given the scarcity of P. Our findings on scenario-specific synergies and trade-offs can aid the management of N- and P-cycling networks in China by reducing chemical fertilizer use and food waste, for example.
Keywords: Čína; odpadky - odstraňování; fosfor; Resilience, Psychological; psychická odolnost; Phosphorus; Food; China; Refuse Disposal; potraviny; dusík; Nitrogen